Challenges in C-14 dating towards the limit of the method inferred from anchoring a floating tree ring radiocarbon chronology to ice core records around the Laschamp geomagnetic field minimum - Muscheler, Raimund; Adolphi, Florian; Svensson, Anders (Earth and Planetary Science Letters, 2014)
The C-14 dating method is the cornerstone for inferring age estimates for natural archives covering the last 50 000 yrs. However, C-14 age calibration for the last ice age relies mostly on records that only indirectly reflect the atmospheric C-14 concentrations. In consequence, calendar age estimates are significantly more uncertain for the period of the last ice age compared to the past 14000 yrs where tree-ring based calibration records exist. Here we connect a C-14 tree-ring chronology from Kauri trees in New Zealand to ice core Be-10 records via the common signal in the galactic cosmic ray flux around the period of the Laschamp geomagnetic field minimum (ca. 41 000 yrs BP). Synchronous changes of modelled C-14 and C-14 inferred from U/Th-dated speleothems support the ice core chronology independently and suggest that the published ice core time scale errors are rather conservative for this period. Our analysis puts C-14 age determinations directly into the context of ice core climate records and it shows that the C-14 records underlying the C-14 calibration curve overestimate the atmospheric C-14 concentration by more than 200 parts per thousand. Consequently, C-14 age calibration presently yields too old calendar age estimates by about 1200 yrs for this period. (C) 2014 Elsevier B.V. All rights reserved.